Transformasi digital dan manajemen perubahan di Institut Agama Islam Tafaqquh Fiddin Dumai - Agustia, Dwi Putri; Mufidah, Nuril; Winingrum, Hani (TA`DIBUNA, 2025)
This study examines change management practices at the Islamic Education Institute Tafaqquh Fiddin (IAITF) Dumai in response to challenges emerging from the digital transformation era. The research focuses on the institution's limited technological infrastructure, low digital literacy among educators, and resistance to change. A qualitative approach with a case study design was employed, utilizing in-depth interviews with administrators and educators. The findings reveal that while technological adaptation is progressing, a systematic and collaborative change management approach remains underdeveloped. Kurt Lewin’s change management model, emphasizing the stages of unfreezing, changing, and refreezing, served as the analytical framework. The study underscores the need for continuous digital skills training, strategic investment in technological infrastructure, and a participatory approach to foster wider acceptance of change. These recommendations aim to enhance the institution’s adaptability to technological advances and contribute to the broader discourse on Islamic education management in the digital era, offering practical insights for similar institutions. AbstrakPenelitian ini mengkaji manajemen perubahan di Institut Agama Islam Tafaqquh Fiddin (IAITF) Dumai dalam menghadapi tantangan era transformasi digital. Fokus penelitian terletak pada keterbatasan infrastruktur teknologi, rendahnya keterampilan digital pendidik, serta resistensi terhadap perubahan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara mendalam terhadap pengurus dan pendidik. Hasil temuan menunjukkan bahwa adaptasi terhadap teknologi telah berlangsung, namun belum diikuti dengan pengelolaan perubahan yang sistematis dan kolaboratif. Model manajemen perubahan Kurt Lewin digunakan sebagai kerangka dalam analisis, menekankan pentingnya tahapan unfreeze, change, dan refreeze. Penelitian ini merekomendasikan perlunya pelatihan digital berkelanjutan, investasi infrastruktur, serta pendekatan partisipatif untuk memperkuat penerimaan perubahan. Temuan ini diharapkan dapat memberikan kontribusi dalam pengembangan manajemen pendidikan Islam yang adaptif terhadap era digital dan menjadi referensi strategis bagi lembaga pendidikan Islam lainnya.